Codificación y descodificación en el discurso televisivo - Hall, Stuart (CIC. Cuadernos de Información y Comunicación, 2004)
This legendary article puts for the first time in the centre of the communication' s debate the asymmetry between the process of encoding and decoding in emission and reception in massive communication. Analysing how denotative significations can have different functions and they can hide some aspects to each audience, and how connotative significance have broad ideological, social and cultural aspects that are important to be competent about to understand the messages, the author gives as TV examples and alerts about the danger of developing a study of communication too for malist, but also recommends the necessity of distinctions between the different pro cess of expression and interpretation of messages.
Keywords: encoding; decoding; connotative; denotative meanings; cultural frames; social; ideological context and communication; TV; iconical signs